SINGO ULUNG DESIGN AS MODERNIZATION MARKETING OF KI RONGGO EARTH BATIK - Meidiyanto, Naufal Maulana (International Conference on Humanity Education and Society (ICHES), 2024)
Looking at the archipelago which is very diverse in style. Indonesia is known by its nickname, the equatorial emerald, whose territory stretches from Sabang to Merauke, has a lot of cultural arts and local wisdom. This is based on the geographical location of the unitary Republic of Indonesia which is very strategic. In addition, Indonesia also has biological and non-biological cultures. This supports the diversity of culture and local wisdom. One of the regions in Indonesia that is rich in local wisdom is East Java, one of the regions or cities in East Java is Bondowoso Regency. This study used a qualitative method with an interactive model data analysis plan. Bondowoso Regency, also known as Bumi Ki Ronggo, is famous for its local wisdom such as Singo Ulung art, Konah Topeng Dance, and Batik products with Bondowoso specialty. This research implements the Singo Ulung design into batik. This is also related to efforts to improve the quality and quantity of Local Branding in the community, especially for UMKM (Usaha Mikro Kecil Menengah) in Bondowoso Regency.